The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1021/cm050537h
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Oxygen Ion Conductors Based on Nd4GeO8 and Nd3GaO6

Abstract: New oxygen ion conductors have been prepared by substituting Ga3+ for Ge4+ in Nd4GeO8, Zn2+ and Mg2+ for Ga3+ in Nd3GaO6, and Ca2+ and Sr2+ for Nd3+ in Nd3GaO6. A combustion technique using ethylenediamine tetraacetic acid has been developed to synthesize these materials at ∼900 °C, leading to powders with spherical particles of about 100−200 nm. The green pellets obtained through the combustion-synthesized powders could be sintered to ∼98% at 1250 °C. It was found that Nd4Ge1 - x Ga x O8 - x /2 are formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…However, earlier, a few experimental studies on some derivatives of these species have also been carried out by researchers. Purohit et al had reported the Nd 3 GaO 6 -based system as a new family of oxide-ion conductor . They tested Ca 2+ and Sr 2+ as dopants at Nd site and found an enhancement in the conductivity by more than 3 orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, earlier, a few experimental studies on some derivatives of these species have also been carried out by researchers. Purohit et al had reported the Nd 3 GaO 6 -based system as a new family of oxide-ion conductor . They tested Ca 2+ and Sr 2+ as dopants at Nd site and found an enhancement in the conductivity by more than 3 orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Purohit et al had reported the Nd 3 GaO 6 -based system as a new family of oxideion conductor. 45 They tested Ca 2+ and Sr 2+ as dopants at Nd site and found an enhancement in the conductivity by more than 3 orders of magnitude. A recent study was also carried out on the synthesis and electrical properties of alkali-earthsubstituted Gd 3 GaO 6 oxide-ion and proton conductors, 46 and it shows a total oxide-ion conductivity at 800 °C, σ 800 °C = 1 × 10 −2 S cm −1 , for the highest substitution level of Ca 2+ .…”
Section: ■ Introductionmentioning
confidence: 99%
“…The high transport number of the oxide ion can be expected in Ga-containing oxides due to the d 10 electron configuration of the Ga 3+ cation. Many gallates such as La 0.8 Sr 0.2 Ga 0.8 ­Mg 0.2 O 3−δ , , La 1.54 Sr 0.46 Ga 3 O 7.27 , , BaLaGaO 4 , , LaSrGaO 4 , and Nd 3 GaO 6 have been reported to exhibit high oxide-ion conductivities. However, these materials contain not only expensive Ga species but also expensive rare-earth elements as essential elements, which may restrict the mass production to satisfy the demands for cost cutting.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, oxide-ion conductors that exhibit high performance at intermediate temperatures (773–973 K) are required to meet the demands of numerous applications and improve device lifetimes . To achieve this, the discovery of new oxide-ion conductors has been investigated using combinatorial chemistry, computational science, and material informatics. …”
Section: Introductionmentioning
confidence: 99%
“…For EuKGe 2 O 6 , no properties except the crystal structure, which features isolated units of three corner-linked GeO 4 tetrahedra ([Ge 3 O 9 ] 6– unit), have been reported . Ca 3 Fe 2 Ge 3 O 12 features a garnet-type crystal structure comprising isolated GeO 4 tetrahedra and exhibits antiferromagnetism as well as spin glass behavior due to Cr doping. ,, BaCu 2 Ge 2 O 7 is a one-dimensional Heisenberg-type antiferromagnetic material with a crystal structure featuring units of two corner-linked GeO 4 tetrahedra ([Ge 2 O 7 ] 6– unit). ,− It is interesting to determine the effect of each GeO 4 tetrahedra in the structure on oxide-ion conductivity. , …”
Section: Introductionmentioning
confidence: 99%